Predictors of Adopting Precautionary Practices in Saudi Community During COVID -19 Pandemic - Alsayali, Mashal; Abdulrashid, Ola A.; Ibrahim, Adel; Al-Osaimi, Matoug Mohammed; Dashash, Noha; Al-Raddadi, Rajaa (American Journal of Psychology, 2020)
Purpose: The massive spread of the new coronavirus, starting from China, continues to threaten the lives of populations worldwide. With no available treatment or vaccine, precautionary behaviors remain the principle preventive measure against the disease. The current study aimed at exploring the factors predicting adherence and adoption of individuals to the recommended precautionary practice in Saudi Arabia. Methodology: Through a cross-sectional design, using a predesigned questionnaire distributed through social media and targeting general adult Saudi population, 1860 individuals responded in almost two weeks. The used questionnaire included, in addition to demographic characteristics, perception of the respondents to the seriousness of the disease, and their compliance with the recommended protective measures of Covid-19. Findings: The total respondents were 1860, among which 1680 individuals responded within the first week of the study (March 2020). The majority of responders were Saudi (90.4%), with marked dominance of females (74.1%), and their mean age was 39.2± 11.6 years. Slightly more than one-half of the respondents (57.2%) agreed that Covid-19 is a serious disease. The perception of participants about the seriousness of Covid-19 was significantly higher among retired individuals p<0.05. Those who perceived Covid-19 as a serious disease were significantly keener to comply with the recommended protective measures against Covid-19. Two-thirds of the respondents (65.8%) expressed that they are worried that the spread of the disease may become worse, and 15.1% always feel afraid to get the disease. Those who felt fearful of getting the disease were significantly more compliant with the protective measures. The primary source of information about Covid-19 was MOH (1164, 62.6%). Unique contribution to theory, practice and policy: Perception of the seriousness of the disease and fear of getting the disease are significant predictors for compliance with recommended protective measures, although it could be beneficial during pandemics; however, the consequences of long-standing worry and fears should be taken into consideration of the health care providers.